TOURISM SATELLITE ACCOUNT, A STATISTICAL TOOL TO ANALYSE TOURISM ROLES - Made Wiyasha, Ida Bagus (JURNAL KEPARIWISATAAN, 2004)
This article tries to explore Tourism Satellite Account (TSA) results in severalcountries. It is a statistical tool used to derive tourism multiplier in a countryseconomy. In preparing a TSA an input-output model is applied. Resultsshow differences in tourism roles in a countrvs economy due to the sizeand leakage in tourism